Tinjauan Penyebab Klaim Pending Pasien Badan Penyelenggara Jaminan Sosial (BPJS) Rawat Inap di RSUD Kembangan Jakarta Barat - Iman Harapan Jaya Zalukhu; Deasy Rosmala Dewi; Daniel Happy Putra (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Financing activities at Kembangan Regional Hospital are dominated by BPJS Health Participants, when submitting claim from patients participating in BPJS Health, there are still delays in submitting claim which will have an impact on hospital operational activities. The aim of this research was to determine the causes of Pending Claims that accurred at Kembangan Regional Hospital. This study used a descriptive method with a mix method approach. The BPJS Health claim procedure for inpatient services at Kembangan Hospital is in accordance with the exiting Standar Operating Procedures. The data used are pending claim files originating from inpatient treatment in November 2022- Jaunary 2023. The research result found 941 inpatient claim files and 84 pending claim files. The cause of pending claim were classified into 7, Conformity between surgical procedures was 22 (26%), inaccuracy in administrative verification and SEP suitability in inputting data into INA-CBGs was 19 (23%), coding determined by the coder was not unbundled by 17 (20%), INA-CBG codes was 9 (!1%), DPJP daognostic code matching 6 (7%), Hospital code conformity 6 (7%), and finally redmissions for the same disease coding 5 (6%). Based on the 5M identification, there are factors, namely the man factor: because the claim file was not accepted by BPJS Health due to coding. The coding given by the hospital to the hospital to the BPJS was not appropriate. Material: supporting files which arrived late on the specified day. Meanwhille, the 3 other factors, namely the money machine and methid, were not obstacles or causes fot the return of the claim files. It is recommended to reevaluate and socialize the reasoms fpr returning BPJS Health claims so that the BPJS Health claim submission process is carried out well and accepted.